Molecularly imprinted polymer nanoparticles for the recognition of ellagic acid - Yucel, Necla; Gulen, Hatice; Hatir, Pinar Cakir (WILEY, 2022)
Ellagic acid (EA) is one of the bioactive polyphenolic flavonoids found in many fruits. Over the years, various extraction methods have been developed to isolate pure EA from plant samples. These methods, however, have some disadvantages, such as low specificity and selectivity, not easy incorporation into industrial processes, and low-purification efficiency. The present study proposes an approach based on the molecular imprinting technique. We describe the nanoscale production of EA imprinted polymers for the first time. We develop a straightforward, efficient, and environmentally friendly precipitation polymerization method to synthesize molecularly imprinted polymer nanoparticles (nanoMIPs). To increase the affinity of nanoMIPs, we explore molecular interactions between EA and functional monomers before polymerization. The nanoMIPs are successfully synthesized with an excellent yield of 94.5%. The maximum binding capacity is 66.6 and 45.6 mu mol/g for EA imprinted and nonimprinted polymers, respectively. Furthermore, in the presence of quercetin, an EA analog, and other compounds in the pomegranate peel extract solution, nanoMIPs selectively retain EA. NanoMIPs will be a valuable analytical tool for separation and sensing applications, especially dispersive solid-phase extraction.
Keywords: biomimetic; nanostructured polymers; separation techniques; SOLID-PHASE EXTRACTION; PERFORMANCE LIQUID-CHROMATOGRAPHY; MAGNETIC NANOPARTICLES; WATER SAMPLES; PURIFICATION; PRECONCENTRATION; MICROSPHERES; Polymer Science